Q: What is the answer for 6(h plus 4) -2h?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

2h + 2h + 2h = 6h

- 3h - 2h + 6h + 9 = h + 9

6h 8min

22h plus 3

6h+4g

3tx + 6t + 3hx +6h = 3(tx + 2t +hx +2h) = 3[t(x + 2) + h(x + 2)] = 3(x + 2)(t + h)

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".

h + 6h = 7h

6h 10m - 3h 45m = 2h 25m

If you mean: 6h+7 then 6*5 plus 7 = 37

It is: 11h

This is a linear equation with one unknown and can be solved as follows. 6h + 2 = 1.......subtract 2 from both sides 6h = -1............divide both sides by 6 h = -1/6.